Very Good Standard (Pavel Skopal /ed./, Naplánovaná kinematografie. Český filmový průmysl 1945 až 1960) - Franc, Martin (Iluminace, 2012)
Review of the publication Planned cinematography: the Czech film industry 1945 to 1960.
Keywords: film literature; post-war cinema; planned economy; review